Industrial water quality requirements - Manivasakam, N. (Chemical Pub. Co., 2011)
"The intention of writing this book is to provide comprehensive information on the quality requirements of water for each industrial use in a single volume. Almost all the major wet processing industries and quality requirements of water for such industrial processes are described ... For easy understanding this book is divided into five parts, namely, 1) Introduction, 2) Impurities present in Water and their Effects on Industrial Uses, 3) Industrial Waters and their Quality Requirements, 4) Drinking and Irrigation water and 5) Impurities present in Water and their Effects on Water Treatment Systems."--Introduction.